Language Variation Analysis in Social Media: A Literature Review on Code-Switching Phenomena among Indonesian Millennials - , I Gusti Ngurah Gede Setia Widiana; I Ketut Suardana; I Made Juliarta (Universitas Bali Dwipa, 2025)
This literature review examines code-switching phenomena among Indonesian millennials in social media contexts, synthesizing existing research to understand patterns of language variation and multilingual communication practices in digital environments. The study employs a qualitative library research methodology, analyzing peer-reviewed academicsources published between 2010-2024 from major databases including Scopus, Web of Science, and Google Scholar. The review identifies three primary code-switching patterns: intra-sentential, inter-sentential, and tag-switching, with Indonesian millennials demonstrating sophisticated multilingual competence across platforms. Key findings reveal that code-switching serves multiple functions including social identity construction, emotional expression, and audience accommodation, with significant variations across different social media platforms. Instagram exhibits high English-Indonesian mixing for aesthetic and global appeal, Twitter shows complex multilingual combinations due to character constraints, Facebook demonstrates more formal patterns for diverse audiences, and TikTok enables innovative multilingual performances. The analysis reveals that theoretical frameworks such as Markedness Theory, Social Network Theory, and Identity Theory require adaptation for digital contexts. Significant research gaps include insufficient longitudinal studies, limited regional comparative analysis. The review concludes that Indonesian millennials use code-switching as a deliberate communicative strategy rather than linguistic deficiency, challenging traditional deficit models and supporting additive multilingualism perspectives. These findings have important implications for educational policy, cross-cultural communication training, and digital literacy development, suggesting the need for more inclusive language policies that recognize multilingual digital competencies as valuable linguistic resources